Bleaching Materials and Tooth Whiteners. Adopted by the FDI General Assembly: 26 August 2005 Montréal, Canada - FDI, POLICY STATEMENT; STANOWISKO, PTS (Journal of Stomatology, 2015)
Dental bleaching materials and whiteners are intended to remove both intrinsic and/or extrinsic tooth stains. Professional in-office tooth whitening products have been used in dentistry for more than a century. In contrast, at-home tooth whitening products intended for patient use under limited professional supervision were introduced to the dental profession in 1989. There are 2 types of professional bleaching or whitening systems that are currently available for treating natural teeth, 1) in-office whiteners administered by dental professionals or 2) home-use products that are issued to patients for in-home use under the dentist’s supervision. Currently, the most commonly used professional formulations are gel preparations of hydrogen or carbamide peroxide.In recent years a variety of over-the-counter (OTC) products, formulations and delivery systems have been introduced to the profession and general public. There is ongoing controversy and confusion as to whether whitening products should be regulated as cosmetic or therapeutic devices; or if dental bleaches and whiteners should be sold directly to the consumer or used without direct professional supervision.